Sustainable Design and Postindustrial Society: Our Ethical and Aesthetic Crossroads - Bachman, Leonard (Enquiry The ARCC Journal for Architectural Research, 2016)
Mid-20th century transitions from industrial product society to postindustrial information society have marked profound but now familiar conversions to service economy, knowledge workers, and cybernetic reasoning. Second order, but equally important consequences of this change involve the transformation from predominantly human-machine heroics to human-human collaboration. Collectively, these events have revolutionized the bases of production and value across the developed world. Less appreciated however, are the more subtle shifts of postindustrialism and their ultimate epochal transformations of contemporary life. The short list of these more elusive transitions includes local scale isolation to macro and global scale interaction, mechanistic routine to systemic reasoning, static to dynamic assumptions, short-termism to scenario planning, profit to value motives, hero to team attribution, intuitive to cybernetic decisions, and a move away from rote procedural expertise in favor of reasoned principle, wisdom, and theory. Our historical perspective thus argues for the relevance of postindustrial society in the emergence of a sustainable future, with particular reference to the built environment and to the complex, collaborative, evidence based and cybernetic processes it involves. The difficulty here is that without a vivid and operational understanding of the aesthetic connections and ethical mandates inherent in these more sublime postindustrial events; it is entirely possible that all the best scientific, technical, and political efforts toward sustainability are hampered by old habits of piecemeal procedures, mechanistic approaches, individual expertise, quick profit, and simplistic short-termism. Postindustrial ethics and aesthetics, on the other hand, offer a new and different apparatus by embracing complexity and dynamic interaction. Within that new aesthetic lies a set of principles and sensitivities towards postindustrial and sustainable era ethics. As such, this present argument attempts to form a cohesive framework contextualizing sustainability, societal trends and nascent evolutions within an aspirational agenda. The underlying theory of this framework describes, explains, and predicts the co-evolution of sustainability and postindustrial events. Finally, the aesthetic basis of the theory is functionally aligned with human cognition. Just as humankind did not quit building with masonry at the end of the Stone Age however, the argument presented here does not demonize the progress of the industrial era that has doubled life expectancy in the last hundred years; nor does it belittle the advent of antibiotics, space travel, telecommunications, rapid transit and the like. It is now necessary however to acknowledge that the pioneer era nature-as-antagonist and industrial era of nature-as-resource have given way to an era of nature-as-model-and-host relation.